Measurements of Doppler and delay spreading of communication signals in medium depth and shallow underwater acoustic channels - Caley, Michael; Duncan, Alexander; Ghiotto, Allesandro (Acoustical Society of Australia, 2012)
Recent measurements of Doppler and delay spreading of underwater acoustic communication signals are presented for 84m and 14m deep marine environments off the coast of Perth, Western Australia. The data-sets are being utilised to develop a computer model of the transient Doppler and delay spreading effects of surface waves. The work supports the on-going development of a dynamic underwater acoustic communication channel simulator to assist the testing of modems and signalling strategies in varied conditions in a cost-effective manner.